The Role of Built Environment's Physical Urban Form in Supporting Rapid Tsunami Evacuations: Using Computer-Based Models and Real-World Data as Examination Tools - León, Jorge; Mokrani, Cyril; Catalán, Patricio; Cienfuegos, Rodrigo; Femenías, Carolina (Frontiers in Built Environment, 2019)
Cities are increasingly becoming hot-spots for nature-originated disasters. While the role of the urban built environment in fostering disaster resilience has been recognized for some time, it has been difficult to translate this potential into practice. This is especially challenging in the case of rapid onset crises such as near-field tsunamis when appropriate urban forms have to support the populations’ ability to autonomously carry out safe and timely responses. In this respect, much of current research remains focused on large-scale elements of urban configuration (streets, squares, parks, etc.) through which people move during an emergency. In contrast, the critical micro-scale of evacuees’ experiences within the built environment is not commonly examined. This paper addresses this shortfall through a macro- and micro-scale analysis of a near-field tsunami scenario affecting the city of Viña del Mar, Chile, including a mixed-methods approach that combines computer-based models and fieldwork. The results show significant macro-scale tsunami vulnerability throughout major areas of the city, which nonetheless could be mitigated by existing nearby high ground and an urban form that allows short evacuation times. However, micro-scale outcomes show comparatively deficient spatial conditions that during an emergency might lead to dangerous outcomes including bottlenecks, falls and panic. Vertical evacuation, in turn, is confirmed as a suitable option for reducing vulnerability, but further examination of each shelter’s characteristics is required.